Non-alcoholic Wernicke's encephalopathy: toxic ingestion or an honest mis-steak? - Salahuddin Nasir; Moustafa Abou Areda; Elise L. Ma; Robert D. Chow; Avelino Verceles; Carol Chiung-Hui Peng (Greater Baltimore Medical Center, 2021)
A 21-year-old male presented with a 2-week history of nausea and non-bloody, non-bilious vomiting, accompanied by diffuse chronic myalgia. The patient endorsed headaches, dizziness, and diplopia that had started one day prior to admission. The patient had consumed a meat-only diet for the prior year. The patient was found to have a high anion gap metabolic acidosis with a superimposed normal anion gap metabolic acidosis in the setting of a several-month history of ingesting multiple naturopathic substances as well as recent use of disulfiram for management of his chronic myalgia. Magnetic resonance imaging (MRI) of the brain demonstrated symmetric hyperintensity involving bilateral thalami, periventricular regions, putamina, pons and medulla, with sparing of the mammillary bodies, consistent with Wernicke's encephalopathy (WE). The patient was treated with intravenous thiamine, a balanced nutritional diet, and hydration. Over the ensuing four days, his metabolic derangements resolved and a repeat MRI demonstrated significantly decreased FLAIR signal abnormality.